Sol-gel Preparation of Silan based Zirconia Hybrid Thin Film - EVCİN, Atilla and GÜNEY, Harun and BEZİR, Nalan (International Journal of Computational and Experimental Science and Engineering, 2021)
The sol-gel process is an innovative advanced method, initially developed to synthesize glass and ceramics at low temperature. Sol-gel process can be used to synthesis materials with a variety of shapes, such as porous membranes, thin fibers, nano-size powders and thin films. In this study, epoxy and methacrylate based silane coupling agents are used together with zirconium oxide to form a hybrid coating system on glass surface. In the experimental study, an organic–inorganic molecular hybrid compound was prepared by sol-gel method. First glasses were cleaned by traditional piranha solution (3:1 H2SO4 : H2O2) to remove contaminants. Silanization was applied to increase the adhesion of hybrid coatings on glass substrates. Glass substrate was coated with this solution by a homemade dip-coater. In this study, (3-Glycidoxypropyltrimethoxysilane, GLYMO and 3-(trimethoxysilyl)propylmethacrylate, TMSPM) were chosen as a silane. Zirconia is inorganic component of hybrid materails. Coated samples were characterized by Fouirer Transform Infrared Spectrophotometer (FTIR), Scanning Electron Microscope with Energy Dispersive X-ray Spectroscopy (SEM-EDX) and Contact Angle Goniometer.